Highly efficient compact verifiable shuffle scheme based on QA-NIZK proof - Xiao-gang CHENG; Jian WANG; Yong-hong CHEN (Tongxin xuebao)
To protect the privacy of voters in e-voting,votes should be shuffled by a series of mix servers.To guarantee the honesty of mix servers,verifiable shuffle scheme was needed.However the proof size of existed CVS (compact veri-fiable shuffle) scheme was dependent on the number of mix servers and the number of voters,which could be very ineffi-cient when there were lots of mix servers and voters.A new CVS scheme was presented with the proof size of only O(1),i.e.constant no matter how many mix servers and voters were involved.The construction is based on an efficient proof system QA-NIZK (quasi-adaptive non-interactive zero knowledge) presented recently.It also points out that the QA-NIZK proof system is malleable,which is of independent interest.